Կորուսյալ հայրենիքի բազմաձայնությունը Պ.Սևակի պոեզիայում․ «Անլռելի զանգակատուն», «Եռաձայն պատարագ» - Հովհաննիսյան, Ն.
Статья посвящена внутренним особенностям и идеологической ценности патриотической поэзии Паруйра Севака, которая является ценным вкладом в национальное устное творчество и в новый виток развития народа в истории. В истории образной мысли, Севак был первым, кто термином «убийство нации» придал политико-правовую окраску геноциду 1915 года. Образ «Несмолкающей колокольни» - это национальная память о геноциде и голос справедливого требования, единства: Комитас–геноцид и захваченная отчизна. The article is devoted to the internal characteristics and ideological values of patriotic poetry Paruyr Sevak, which is a valuable contribution to the national story-telling and a new round of growth in the history of the people. In the history of imaginative thought, Sevak the first has given the legal and political coloration of genocide of 1915 by the term «murder of the nation». The image of «The incessant bell» is the national commemoration of the genocide and the voice of the just demand, of the unity: Komitas, genocide and captured homeland.
Keywords: Գրականագիտություն